Estimates of mammography coverage according to health surveys in Brazil - Viacava, Francisco; Souza-Junior, Paulo Roberto Borges de; Moreira, Rodrigo da Silva (Revista de Saúde Pública, 2009)
OBJECTIVE: Population surveys constitute an essential tool to monitor mammography coverage and factors associated with its performance. Estimates tend to be overestimated in surveys based on the population living in households with a telephone. The study aimed to estimate mammography coverage from population-based surveys. METHODS: Based on mammography coverage levels in women aged between 50 and 69 years, with and without a fixed telephone line, from the Pesquisa Nacional por Amostra de Domicílios 2003 (PNAD - 2003 National Household Survey), ratios between these coverage levels and their respective variation coefficient were calculated. The coverage ratio was multiplied by the coverage estimated by the Vigilância de Fatores de Risco e Proteção para Doenças Crônicas por Inquérito Telefônico (VIGITEL - Telephone-based Surveillance of Risk and Protective Factors for Chronic Diseases), enabling coverage in women without telephones in 2007 to be estimated. These estimates were applied to the female population, with and without a telephone, obtained from the PNAD 2006, thus achieving the final estimates for the capitals. RESULTS: In 2007, mammography coverage was estimated at about 70% for the group of capitals, varying from 41.2% in Porto Velho (Northern Brazil) to 82.2% in Florianópolis (Southern Brazil). In 17 cities, coverage was higher than 60%; in eight, between 50% and 60%; and in two, below 50%. In absolute terms, the difference between VIGITEL coverage levels and those estimated was 6.5%, varying from 3.4% in São Paulo (Southeastern Brazil) to 24.2% in João Pessoa (Northeastern Brazil). CONCLUSIONS: Differences in magnitudes of mammography coverage estimates for population surveys are mostly a reflection of study designs. In the specific case of mammography, it would be more appropriate to estimate its coverage by combining VIGITEL data with those from other surveys that include information about women with and without a fixed telephone line, especially in cities with low fixed telephone line coverage.